Role of inflammatory cells in airway remodeling in COPD - Wang,Y; Xu,J; Meng,Y; Adcock,IM; Yao,X (International Journal of Chronic Obstructive Pulmonary Disease, 2018)
COPD is characterized by chronic bronchitis, chronic airway obstruction, and emphysema, leading to a progressive and irreversible decline in lung function. Inflammation is central for the development of COPD. Chronic inflammation in COPD mainly involves the infiltration of neutrophils, macrophages, lymphocytes, and other inflammatory cells into the small airways. The contribution of resident airway structural cells to the inflammatory process is also important in COPD. Airway remodeling consists of detrimental changes in structural tissues and cells including airway wall thickening, epithelial metaplasia, goblet cell hypertrophy, and smooth muscle hyperplasia. Persistent airway inflammation might contribute to airway remodeling and small airway obstruction. However, the underlying mechanisms remain unclear. In this review, we will provide an overview of recent insights into the role of major immunoinflammatory cells in COPD airway remodeling.